2009
DOI: 10.1007/s10549-009-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw and use of bisphosphonates in adjuvant breast cancer treatment: a metanalysis

Abstract: To estimate the cumulative randomized evidence for the overall incidence of bisphosphonates induced jaw osteonecrosis in adjuvant treatment of breast cancer. Systematic review and meta-analysis of randomized clinical trials. Trials were located through PubMed, ISI, Cochrane Library, and major cancer scientific meetings searches. We identified 15 studies reporting data on osteonecrosis of the jaw. A total of 10,694 randomized women were included, of whom 5,312 received bisphosphonates and 5,382 received either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
62
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 33 publications
2
62
1
2
Order By: Relevance
“…They concluded that prospective epidemiological efforts, such as those made by academic researchers, are probably the most reliable source of information regarding ONJ incidence [2]. Thus, Mauri et al [1] may report on a low incidence of ONJ in those patients receiving bisphosphonates as adjuvant treatment of breast cancer, simply because the RCTs at study have not been able to detect ONJ cases, similarly to the previous experience with RCTs and ONJ [2]. 3.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…They concluded that prospective epidemiological efforts, such as those made by academic researchers, are probably the most reliable source of information regarding ONJ incidence [2]. Thus, Mauri et al [1] may report on a low incidence of ONJ in those patients receiving bisphosphonates as adjuvant treatment of breast cancer, simply because the RCTs at study have not been able to detect ONJ cases, similarly to the previous experience with RCTs and ONJ [2]. 3.…”
mentioning
confidence: 93%
“…One should read with great interest the paper of Mauri et al [1] in the Online First section of Breast Cancer Research and Treatment. The paper presents a meta-analysis of the existing randomized clinical trials (RCTs) for the overall incidence of bisphosphonates-induced jaw osteonecrosis (ONJ) in adjuvant treatment of breast cancer.…”
mentioning
confidence: 99%
See 3 more Smart Citations